Hidden city travel and its impact on airfare: The case with competing airlines. (February 2022) - Oh, Jaelynn; Huh, Woonghee Tim
Abstract: Hidden city pricing is an anomaly in airline pricing where a direct flight from A to B is more expensive than a multi-leg flight from A to B and B to C. In this case, customers wanting to travel from A to B may consider purchasing the connecting flight from A to C, deplane in B, and throw away the second leg of the itinerary. This practice is called hidden city ticketing. We study the cause and the impact of hidden city ticketing. The airline industry has perceived this practice harmful to profitability and has taken measures to discourage such practice. We build a stylized model where two airlines compete on a hub-and-spoke airline network and use a game theoretic approach to study airline and consumer decisions. We find that hidden city pricing can arise when an airline lowers the price of its indirect flight to compete with the competitor's direct flight on the same route. We also find that strategic customers who seek hidden city traveling opportunity can attenuate competition by limiting the airlines' ability to lower their price for connecting flights. Thus, when customers in the market start practicing hidden city ticketing, airlines face less competition and may be able to charge higher prices. Our results provide future-looking perspective on what may happen to the equilibrium airfare if customers start practicing hidden city ticketing. Highlights: Hidden city pricing can arise when an airline lowers its connecting flight fare to price compete with the competitor's direct flight on the same route. Customers seeking hidden city travel opportunities limit an airline's ability to charge a low price to its connecting flight. Strategic consumers who seek hidden city travel opportunities can work as a mechanism for the airlines to avoid severe price competition resulting in higher airline profits.